MEASURING THE IMPACT OF SKILL-BASED MATERIALS ON STUDENTS’ WORK-RELATED LANGUAGE SKILLS - Hafizhatu Nadia; Dina Rafidiyah; Yansyah Yansyah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The requirement to have good English skill is inevitably necessary to widen our students’ opportunities to go International. In the ESP class, the materials taught need to be specified so this goal can be effectively achieved. The present paper measures the impact of skill-based materials for nursing students on their work-related language skills. There were 15 students from D-3 International Nursing Program at University of Muhammadiyah Banjarmasin who joined this research. The research method applied was pre-experimental in which the researchers measures the impact of before and after the materials applied in the subject. Test and observation became the primary instruments to assess the effect. The materials were experimented for four meetings before the post-test was conducted. The observation was carried out to notice the students’ responses during the lessons. The findings showed that most of the students’ have better work-related language skills after the materials applied in the classroom. Notes from the observation also told the subjects were active and highly motivated to participate in the lessons.